2012
DOI: 10.1371/journal.pone.0052977
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human SUV39H1 Chromodomain and Its Recognition of Histone H3K9me2/3

Abstract: SUV39H1, the first identified histone lysine methyltransferase in human, is involved in chromatin modification and gene regulation. SUV39H1 contains a chromodomain in its N-terminus, which potentially plays a role in methyl-lysine recognition and SUV39H1 targeting. In this study, the structure of the chromodomain of human SUV39H1 was determined by X-ray crystallography. The SUV39H1 chromodomain displays a generally conserved structure fold compared with other solved chromodomains. However, different from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…However, recent Clr4 studies in fission yeast demonstrated that not only Swi6 CD but also Clr4 CD showed higher affinity for H3K9 methylation, and this interaction seemed to be crucial for Clr4 accumulation and H3K9me2/3 formation on heterochromatin (33). Furthermore and most recently, it has been reported that Suv39h CD also showed higher affinity to methylated H3K9 (highest to H3K9me3) in vitro (34). Therefore, our new findings and recent information strongly suggest that H3K9me3 deposited by Suv39h can directly tether its own enzyme to pericentric regions.…”
Section: Hp1 Binding To Suv39h1 Was Dispensable For the Establishmentmentioning
confidence: 99%
“…However, recent Clr4 studies in fission yeast demonstrated that not only Swi6 CD but also Clr4 CD showed higher affinity for H3K9 methylation, and this interaction seemed to be crucial for Clr4 accumulation and H3K9me2/3 formation on heterochromatin (33). Furthermore and most recently, it has been reported that Suv39h CD also showed higher affinity to methylated H3K9 (highest to H3K9me3) in vitro (34). Therefore, our new findings and recent information strongly suggest that H3K9me3 deposited by Suv39h can directly tether its own enzyme to pericentric regions.…”
Section: Hp1 Binding To Suv39h1 Was Dispensable For the Establishmentmentioning
confidence: 99%
“…Therefore, it is possible that Suv39h1 also possesses RNA-binding activity, and nascent transcript is involved in creating Suv39h1's target specificity. In addition, it is already known that Suv39h1 CD possesses higher binding affinities for H3K9me2/3 (Wang et al, 2012). In Suv39h DKO cells, pericentric H3K9me3 is severely diminished, but global H3K9me3 is still heavily maintained by other H3K9 methyltransferases (Bulut-Karslioglu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation was considered indirect and mediated by HP1 [52,53]. But SUV39H1 has also been shown self-sufficient for H3K9me3 binding in vitro [54] and in vivo [49,55,44], which is expected in principle since SUV39H1/2, like HP1, have a chromodomain. The partial disruption of heterochromatin by hyperacetylation using Trichostatin A (TSA) treatment, leads to the complete dislocation of HP1 from the residual chromocenters, whereas SUV39H1 still binds them [5].…”
Section: Chromocenter Formation and Suv39h1-hp1 Functional Relationshipsmentioning
confidence: 99%